Factors Influencing Voting Intention for Indonesian People Representative Council Election 2019: The Case of First Voter in Bandung - Martin, Wenty Gafrina; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abstract. This study measures the eight factors adopted from Newman and Sheth's model (1985) that will influence voting behavior intentions in 2019 Indonesian people representative council election, given the moderating effect of the media to strengthen the influence of the eight factors to the voting behavior intentions. A final total of 267 first voters in Bandung that participated in the 2014 Indonesian people representative council election were surveyed using a questionnaire, and the sample from population is taken using a convenience sampling method. Binary logistic regression analysis was performed to test the influences among the research variables. The result of this survey indicated that the proposed factors adopted from Newman and Sheth's model (1985) as the independent variables did not provide a significant impact on first voterâ€™s intention in Bandung for 2019 Indonesian people's representative council election. The object of first voters has a very distinctive characteristics compared with the general voters in the previous research that formed the hypotheses of this study because of the difference in knowledge and information about election, so the research is expected to open new horizons for further research to examine other factors that can influence first voters. The findings will be a beneficial for political parties to ensure the regeneration of political parties and the provision of political education to young generation.Â Keywords: Voterâ€™s Behavioral Intention, Political Party, First Voter.